2007
DOI: 10.1021/ja066633g
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Model System for the Study of Carbohydrate−Aromatic Interactions

Abstract: A molecular scaffold was identified which enables the establishment of intramolecular interactions between a monosaccharide and a nearby phenyl ring. A group of molecules containing four different monosaccharides (glucose, galactose, N-acetyl-glucosamine, and N-acetyl-galactosamine) was synthesized and used to investigate the extent and nature of this carbohydrate-arene interaction, as well as the effect on the overall 3D structure of the molecules involved. The sugar-aromatic distance was evaluated by rigorou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(55 citation statements)
references
References 58 publications
3
52
0
Order By: Relevance
“…However, recently, evidence has come to light for an enthalpically driven 'non-classical' hydrophobic effect and this may play a role in lectin-saccharide binding events [39,40]. Moreover, a variety of model studies have indicated roles for CH-p [41][42][43][44][45] and other apolar interactions [46,47] in carbohydrate recognition. Having said all this, the pattern of polar contacts is surely also important, and it is safest to assume that polar and apolar interactions work in concert to achieve biological carbohydrate recognition.…”
Section: Synthetic Lectin Design Principlesmentioning
confidence: 99%
“…However, recently, evidence has come to light for an enthalpically driven 'non-classical' hydrophobic effect and this may play a role in lectin-saccharide binding events [39,40]. Moreover, a variety of model studies have indicated roles for CH-p [41][42][43][44][45] and other apolar interactions [46,47] in carbohydrate recognition. Having said all this, the pattern of polar contacts is surely also important, and it is safest to assume that polar and apolar interactions work in concert to achieve biological carbohydrate recognition.…”
Section: Synthetic Lectin Design Principlesmentioning
confidence: 99%
“…Dispersion interactions between carbohydrates and aromatic moieties were also detected by solution NMR [15], [23][28] and other experimental methods [29][31].…”
Section: Introductionmentioning
confidence: 99%
“…The carbohydrate-aromatic interactions, which are sometimes denoted as CH/p interactions, were used for recognition of carbohydrates by artificial receptors [11][12][13][14]. The carbohydrate-aromatic interactions have been studied extensively both by experimental [15][16][17][18][19][20][21][22][23] and by theoretical [24][25][26][27][28][29][30][31][32][33][34][35] methods. The carbohydrate recognition processes involve desolvation of water molecules from the carbohydrate molecule.…”
Section: Introductionmentioning
confidence: 99%